Knowledge and Perception of Diabetes Mellitus among Patients with Type 2 Diabetes Mellitus in Five Public Health Centers in Karawang, West Java, Indonesia - Khansa Ainun Nabila; Maya Kusumawati; Ginna Megawati (Althea Medical Journal, 2022)
Background: Diabetes mellitus (DM) is a chronic metabolic disease that causes various complications, leading to a high mortality rate and high medical costs. Good knowledge and perception are essential for patients in understanding the disease and how to prevent the complications. This study aimed to assess the knowledge and perceptions of DM among patients with type 2 DM from the Public Health Centers (Pusat Kesehatan Masyarakat, Puskesmas), the primary health care facility in West Java.Methods: The research design was quantitative observational with a cross-sectional method and descriptive approach. Data were collected in 2019 from all DM patients living in five working areas of the Puskesmas in Karawang Regency, West Java, Indonesia. Data collection was performed by trained interviewers, using a validated translation of the Diabetes Knowledge Questionnaire (DKQ) (Cronbach’s alpha 0.723) and the Brief Illness Perception Questionnaire (BIPQ) (Cronbach’s alpha 0.74) to measure knowledge (24 questions) and to explore perception (8 questions), respectively. Results: Of the 211 respondents, 165 were predominantly female (76.4%) and aged 52–61 years old (35.2%). Knowledge was moderate (55.8%), however, they had a negative perception of the disease (50.9%).Conclusions: Although most of the respondents have a moderate level of knowledge, their perception of DM is still negative. Therefore, education for patients and the community needs to be evaluated to enhance knowledge and perceptions about diabetes mellitus.